Deveelopmnt of Augmented Reality-Based Learning Media in Grade II Elementary School - Pramesti, Angger Winsi; Nugraheni, Anggun; Rahayu, Shinta Dwi (Jurnal Inovasi Pendidikan Dasar, 2023)
This research uses the R&D (Research and Development) method. The application development process uses the ADDIE development model. Data collection techniques use observation techniques, interviews, questionnaires, and pretest-posttest questions. After media product development, validation tests by media and material experts, and product implementation in the implementation of learning in grade II SD N Nirmala, the results showed that Augmented Reality-based fractional learning media in grade 2 elementary school material developed was suitable for use as learning media. This learning media can increase the understanding of grade 2 elementary school students about the basic concept of fractions. With this media, students become more enthusiastic in participating in learning activities.